2022-RA-685-ESGO What is beyond brca mutational status in high grade serous ovarian cancer? The role of hormone receptors expression. (20th October 2022) - Perrone, Emanuele; Tudisco, Riccardo; Pafundi, Pia Clara; Guido, Davide; Ciucci, Alessandra; Martinelli, Enrica; Zannoni, Gian Franco; Piermattei, Alessia; Marchetti, Claudia; Nero, Camilla; Gallo, Daniela; Scambia, Giovanni; et al.
Abstract : Introduction/Background: Several studies have explored the prognostic role of hormone receptor status in high grade serous ovarian cancer (HGSOC). However, few reports have investigated their expression according to BRCA mutational status. Notably, there is evidences of a strong interaction between BRCA1/2 proteins and steroid hormones system, including higher titres of estradiol and progesterone in BRCA1/BRCA2 mutation carriers. Thus, we sought to explore the hormone receptor pattern and its potential prognostic impact in a well-characterized cohort of HGSOC patients stratified for BRCA status. Methodology: We assessed ERα, ERβ1, ERβ2, ERβ5, PR (progesterone receptor) and AR (androgen receptor) expression by immunohistochemistry in a single-centre observational retrospective cohort study of 207 HGSOC women, profiled for BRCA-1/2 mutation status with available clinical and molecular features. Results: 135 BRCA-wild type (BRCA-wt) and 72 BRCA1/2 mutation carriers (BRCA-mut) were observed. No significant differences were detected in hormone receptor expression between the two populations. However, in the subgroup analysis according to menopausal status, a significantly lower ERα expression was found in pre-menopausal BRCA-mut compared to BRCA-wt patients (p=0.02) ( figure 1 ). Regarding survival analysis, none of the examined hormone receptors had a significant prognostic role. However, a higher ERα/ERβ5nuclear ratio differently affected outcome according to BRCA status: positively in BRCA-wt cohort (HR 0.77; CI 0.61–0.96; p=0.019) and negatively in BRCA-mut cohort (HR 1.41; CI 1.06–1.87; p=0.020) ( table 1 ). Finally, higher PR levels were associated with platinum sensitivity in the whole population (p=0.019). Conclusion: This study suggests a potential role of estrogen-mediated pathways in BRCA1/2-associated HGSOC tumorigenesis, revealing a possible therapeutic potential of targeting this interaction.